THE ROLE OF AFRICAN TRADITIONAL RELIGION IN BUILDING COMMUNITY SOLIDARITY AMONG ENUGU-EZIKE PEOPLE - Rowland Olumati (Ph.D); Ugwuanyi, Simeon Chimuanya (Scholar Express Journal, 2025)
The research work underscores the Role of African Traditional Religion in Building Community Solidarity among Enugu-Ezike People. The work explores that African Traditional Religion (ATR) is one of the oldest and most enduring belief systems in the world, deeply embedded in the cultural, spiritual and cosmological worldview of African societies. It is a complex and dynamic system of beliefs, rituals, and practices that have been passed down through generations, primarily through oral traditions. African traditional religion is not merely a religion but a way of life that encompasses the spiritual, social and cultural dimensions of African communities. The methodology adopted in this work is phenomenological approach. The findings revealed that African traditional religion provides a framework for understanding the universe, the relationship between humans and the divine, and the interconnectedness of all living beings. The cosmology of African traditional religion is particularly significant as it offers insights into how African societies perceive the origin, structure and functioning of the universe. The theoretical framework adopted in this work is Emile Durkheim Theory of social order where it says that religion works along with society. The work concludes that Enugu-Ezike, like many other African communities have a rich tradition of oral narratives, myths and rituals that explain their cosmological beliefs and creation stories. These narratives are not merely tales but are integral to the community’s identity, values and worldview. The work recommends that African traditional religion resonates in the life of the people and should be developed in the Nigerian educational curriculum.
Keywords: African Traditional Religion; Community Solidarity; Ritual